A Cu–Pd single-atom alloy catalyst for highly efficient NO reduction. Issue 36 (28th August 2019) - Xing, Feilong; Jeon, Jaewan; Toyao, Takashi; Shimizu, Ken-ichi; Furukawa, Shinya
Abstract : Highly active and selective NO reduction was achieved at low temperatures using a minimum amount of noble metal Pd. Abstract : A series of Cu–Pd alloy nanoparticles supported on Al2 O3 were prepared and tested as catalysts for deNO x reactions. XRD, HAADF-STEM, XAFS, and FT-IR analyses revealed that a single-atom alloy structure was formed when the Cu/Pd ratio was 5, where Pd atoms were well isolated by Cu atoms. Compared with Pd/Al2 O3, Cu5 Pd/Al2 O3 exhibited outstanding catalytic activity and N2 selectivity in the reduction of NO by CO: for the first time, the complete conversion of NO to N2 was achieved even at 175 °C, with long-term stability for at least 30 h. High catalytic performance was also obtained in the presence of O2 and C3 H6 (model exhaust gas), where a 90% decrease in Pd use was achieved with minimum evolution of N2 O. Kinetic and DFT studies demonstrated that N–O bond breaking of the (NO)2 dimer was the rate-determining step and was kinetically promoted by the isolated Pd.